2010
DOI: 10.1158/1078-0432.ccr-09-1924
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2 Promotes Disease Progression of Neuroendocrine Tumors

Abstract: Purpose: Inhibition of angiogenesis represents a promising therapeutic strategy in neuroendocrine tumors. Angiopoietin-2 (Ang-2), a ligand of the endothelial tyrosine kinase Tie-2, is emerging as a key regulator of vascular remodeling during tumorangiogenesis. We therefore addressed the expression and biological significance of Ang-2 in human neuroendocrine tumors. Experimental Design: Surgical specimens and serum from neuroendocrine tumor patients were used to determine Ang-2 expression by in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 42 publications
4
47
1
Order By: Relevance
“…In this study, both progression-free survival and overall survival were reduced in melanoma patients with high levels of circulating Ang2 (using a threshold of 1.8 ng/mL). Finally, a study of neuroendocrine tumors found that the average level of circulating Ang2 increased from 2.6 ng/mL in control samples to 4.0 ng/ mL in patients with neuroendocrine tumors, with values in the cancer group up to 25 ng/ mL (Detjen et al 2010). Again, in this tumor type, higher levels of Ang2 were associated with worse overall survival.…”
Section: Expression Of Ang2 Is Increased In Several Disease Settingsmentioning
confidence: 93%
See 1 more Smart Citation
“…In this study, both progression-free survival and overall survival were reduced in melanoma patients with high levels of circulating Ang2 (using a threshold of 1.8 ng/mL). Finally, a study of neuroendocrine tumors found that the average level of circulating Ang2 increased from 2.6 ng/mL in control samples to 4.0 ng/ mL in patients with neuroendocrine tumors, with values in the cancer group up to 25 ng/ mL (Detjen et al 2010). Again, in this tumor type, higher levels of Ang2 were associated with worse overall survival.…”
Section: Expression Of Ang2 Is Increased In Several Disease Settingsmentioning
confidence: 93%
“…However, several in situ hybridization studies have revealed increased levels of Ang2 expression in cancers of different origin, including neuroendocrine tumors (Detjen et al 2010), hepatocellular cancer (Chen et al 2001;Scholz et al 2007), gastric cancer (Moon et al 2006), angiosarcoma (Brown et al 2000), carcinosarcoma (Emoto et al 2004), and astrocytoma (Zagzag et al 1999). Interestingly, some studies report increased expression of Ang2 in both endothelial cells and tumor cells (e.g., Helfrich et al 2009;Detjen et al 2010), whereas other studies have shown Ang2 expression limited to the vasculature and not in tumor cells (Stratmann et al 1998;Zagzag et al 1999;Moon et al 2006;Goede et al 2010). In addition to in situ hybridization methods, analyses of RNA from whole and microdissected tissue have shown increased Ang2 in tumors versus corresponding normal tissue (e.g., Durkin et al 2004;Helfrich et al 2009;Goede et al 2010).…”
Section: Expression Of Ang2 Is Increased In Several Disease Settingsmentioning
confidence: 99%
“…Poor short term survival was reported with neurokinin A concentrations (>50 pg/ml) (158). Uniform expression of Angiopoietin-2 (Ang-2) messenger RNA (mRNA) described in endothelial cells of both nontransformed pancreatic tissue and pan NET tissue (159).…”
Section: Discussionmentioning
confidence: 99%
“…administration of Ketanest (100 mg/kg) and Rompun (10 mg/kg). For tumor induction, the pancreas was exposed and 1!10 6 BON cells were injected into the head of the pancreas as previously described (Detjen et al 2010). Treatment of engrafted tumors was initiated at week 3 following tumor cell implantation.…”
Section: Bon Net Orthotopic Tumor Modelmentioning
confidence: 99%
“…Both drugs act at least in part via inhibition of tumor angiogenesis, promoting interest in the vascular features of NETs (Alexandraki & Kaltsas 2012). Well-established angiogenic growth factors, such as VEGF-A (Terris et al 1998) or angiopoietins (Srirajaskanthan et al 2009, Detjen et al 2010, are present in NETs. In addition, characteristic neuroendocrine secretion products, including chromogranin A fragments (Corti 2010) and serotonin (Asada et al 2009), affect angiogenesis and vascular permeability, altogether creating a unique stromal microenvironment.…”
Section: Introductionmentioning
confidence: 99%